Efek Pemanfaatan Program Pemantauan dan Promosi Pertumbuhan terhadap Status Gizi Balita di Kota Cirebon - Nurcahyani, Lia; Hakimi, Mohammad; Sudargo, Toto (JURNAL KESEHATAN REPRODUKSI, 2017)
Background: Undernourishment is a key problem of mortality in underfive, inwhich one of the causes is lack of growth monitoring and promotion program utilization. Cases of undernourishment at Cirebon Municipality exceed the provincial and national figures. In 2008, community participation in growth monitoring and promotion program increased 19% from the previous year, however cases of undernourishment also increased 0.23%Objective: To assess the effect of growth monitoring and promotion program utilization toward nutritional status of underfives.Method: The study was observational with retrospective cohort design. Subject consisted of 246 underfives of 17-59 months and mothers that met inclusion and exclusion criteria. Sampling used three stage combined with purposive and random sampling technique. Data consisted of primary and secondary data obtained from questionnaire, growth chard, nutrition registry, monthly report of underfive weighing at Cirebon Municipality 2008, digital scale, length board/ microtoise and WHO anthropometric software. Data analysis used univariate, bivariate with chi square, and multivariate with logistic regression. The study was supported with qualitative data obtained from observation and indepth interview.Result and Discussion: The utilization of growth monitoring and promotion program affected nutritional status of underfives significantly (p<0.05). Incidence of undernourished underfives that did not utilize the program regularly was 2.7 times greater than in those utilizing the program regularly after considering the contribution of knowledge and attitude of mothers and age of underfives. Input indicator especially role of cadres in the process of growth monitoring and promotion program at Cirebon Municipality was not optimum. Constraints in program utilization consisted of individual (health reason), provider (social reason) and community (geographical reason) factors.Conclusion: Monthly growth monitoring was prioritized on underfives for the first 24 month.Target of growth monitoring and promotion program could be achieved when there was comprehensive support from demand side (people that received the service), support side (service providers) and policy side (policy makers).Keywords: nutritional status, underfive, growth monitoring, growth promotion, program utilization